Hubungan Tingkat Pendidikan dan Tingkat Pengetahuan tentang Merokok dengan Derajat Berat Merokok - Arti Tyagita Kusumawardhani; . Reviono; Arsita Eka Prasetyawati (Nexus Kedokteran Komunitas, 2013)
Background: Smoking behavior is one of the most widely spread health problem. Ones smoking behavior is very much determined by ones knowledge of smoking behavior, where as such knowledge is also very much affected by ones level of education. This research aims to determine the correlation between educational level and knowledge of smoking behavior to the severity of smoking habit. Methods: This research is an observational analysis using cross-sectional. The study was conducted in Faculty of Medicine, Sebelas Maret University. The sample was taken using Stratified Random Sampling and Quota Sampling. Approach with male smokers administration staffs, temporary employees, lecturers, and Faculty of Medicine of Sebelas Maret University class 2011, qualifying and disqualifying with inclusion criteria. Data retrieval is done by looking at the patients questionnaires. Data were analyzed using correlative non-parametric Spearman analysis method, with SPSS 17.00 for Windows. Results: There is a positive correlation between ones educational level and the severity of ones smoking habit, with correlation coefficientvalue as much as0.165and significance value(2-tailed)as much as0.208. This findings show that there is a weak and insignificant relation between both variables. Moreover, there is a weak negative correlation between ones educational level and ones knowledge on smoking habit, with significance value(2-tailed)as much as 0.522 and correlation coefficient value as much as 0.078. there is also a negative correlation between ones knowledge of smoking habit and the severity of ones smoking habit, with significance value(2-tailed)as much as 0.589 and correlation coefficient value as much as 0.071. Conclusions: There is not any significant relation between ones educational level and knowledge on smoking behavior to the severity of ones smoking habit. Keywords: Educational level, knowledge of smoking behavior, severity of smoking habit, smoking.